Evaluation of the effect of obesity, dietary glycemic index and metabolic profiles on the cardiovascular risk in children with classical phenylketonuria - Kadıoğlu Yılmaz, Banu; Baykan, Ali; Kardaş, Fatih; Kendirci, Mustafa (Academic Press Inc., 2023)
Objectives: To compare the glycemic index(GI),obesity,echocardiographic,and arterial stiffness measurements with the healthy control group to evaluate the cardiovascular risk of pediatric classical phenylketonuria(PKU). Methods: The study was a prospective observational,involving 104 pediatric volunteers between 2019 and 2020.Two groups were formed:the PKU patient group and the healthy control group.These two groups were further divided into three subgroups:obese,overweight,and normal weight.The patients' anthropometric measurements,body fat analysis,biochemical analysis, GI and glycemic load(GL),arterial stiffness measurements,and echocardiographic findings were recorded. Results: The PKU patient group's glucose,total cholesterol,LDL,and HDL values were significantly lower than the healthy control group(p = 0.010 for glucose and p = 0.001 for total cholesterol,LDL and HDL).Triglyceride levels were higher in the PKU patient group than in the healthy controls(109.6 vs. 76.7 mg/dl,p = 0.001). GI and GL were significantly lower in the PKU patient group than in the healthy control group(GI 453 vs. 392.9,p = 0.017 and GL 101.1 vs. 85.5,p = 0.036).Left ventricular mass(LVM)-z-score and LVM index were significantly higher in the PKU group than in the healthy control group(LVM z-score 0.9 vs. 0.5,p = 0.014 and LVM index 38.9 vs. 32.7 g/m2.7,p = 0.001). A moderately statistically significant positive correlation was found between the mean phenylalanine(phe) value and pulse wave velocity(PWV) among the PKU patient groups(R: 0.477,p < 0.001).A moderately statistically significant positive correlation was also found between waist circumference and PWV in the PKU patient group(R:0.541, p < 0.001). Conclusions: Our study found that close follow-up of phe levels and PWV is more critical than obesity, GI, and GL in the cardiovascular evaluation of classical PKU patients.A large number of multicenter pediatric studies are needed in this area.
Keywords: Arterial Stiffness; Classical Phenylketonuria; Glycemic Index; Glycemic Load; Left Ventricular Mass Index; Pediatric Age